FEATURES OF UNSCENTED KALMAN FILTER PERFORMANCE USING POLAR MEASUREMENTS - P. A. Khmarski; A. S. Solonar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The principle of the unscented transformation and features of Unscented Kalman filter performance using polar measurement is considered. The estimation performance of Extended Kalman filter and Unscented Kalman Filter is compared.